The Role of Formyl Peptide Receptor 1 in Uterine Contraction During Parturition - Chen, Chaolu; Zhu, Shuaiying; Bai, Long; Sui, Meihua; Chen, Danqing (Frontiers in Pharmacology, 2021)
Parturition involves the transformation of the quiescent myometrium to the laboring state, which is driven by changes in myometrial gene expression. This study aimed to identify myometrial transcriptomic signatures and potential novel hub genes in parturition, which have great significance for understanding successful parturition and treating labor pathologies such as preterm birth. In our study, human myometrium was collected from women in spontaneous term labor (TL=8) and term not in labor (TNL=8) to survey transcriptional changes associated with labor by using RNA-seq. We screened the differentially expressed genes (DEGs) of functional enrichment analysis including GO and KEGG pathway analysis and gene set enrichment analysis (GSEA) to study the role of DEGs and potential underlying mechanisms of parturition. Moreover, we used protein-protein interactions network analysis to recognize the hub genes among these DEGs. Furthermore, the biological behavior of hub genes in myometrial contraction was verified by cellular experiments. A total of 582 DEGs were selected. The enrichment analysis revealed that DEGs were enriched in signal transduction, regulation of signaling receptor activity, inflammatory response, cytokine-cytokine receptor interaction, IL-17 signaling pathway, TNF signaling pathway and so on. FPR1 was highly expressed in laboring myometrium. The experimental results showed that activating FPR1 in human myometrial cells, resulted in increased myometrial contraction. The transcriptome analysis of term labor myometrium revealed that labor onset was associated with inflammatory response. Our findings implicate the novel role of FPR1 as a modulator of myometrial contraction.